(untitled) (Estudios de Historia de España, 2016)
Rarely those that are fond of History are aware that the Gipsies arrived to Spain in recent times, in the XVth. Century. It is taken for granted that the Gipsy element is the essence of Spanish culture which has inspired poets and musicians. Such is a mistake. Six hundred years ago they crossed Europe following the routes of religious pilgrimage, wandering as pennants and victims of the Turks. The Gipsies, called Egyptians (Egipcianos), entered European soil through Hungary. Their resistance to sedentary life made them incapable vassals for the Absolute Monarchy, because of which they were persecuted. The winds of Reformation and the ideals of Erasmic thought did not stop intolerance, in contrary it increased Gipsy persecution.